CompTIA security+ study guide : exam SYO-401 - Dulaney, Emmett A., author; Easttom, Chuck, author (Hoboken : John Wiley & Sons, 2014)
Join over 250,000 IT professionals who've earned Security+ certification If you're an IT professional hoping to progress in your career, then you know that the CompTIA Security+ exam is one of the most valuable certifications available.
Measuring and weighing risk -- Monitoring and diagnosing networks -- Understanding devices and infrastructure -- Access control, authentication, and authorization -- Protecting wireless networks -- Securing the cloud -- Host, data, and application security -- Cryptography -- Malware, vulnerabilities, and threats -- Social engineering and other foes -- Security administration -- Disaster recovery and incident response
Includes index.
In English text.
Keywords: Electronic data processing personnel -- Certification; Computer security -- Examinations -- Study guides; Computer networks -- Security measures -- Examinations -- Study guides